Development of ZrFeV alloys for hybrid hydrogen storage system. (13th July 2016) - Cao, Zhijie; Ouyang, Liuzhang; Wang, Hui; Liu, Jiangwen; Sun, Lixian; Felderhoff, Michael; Zhu, Min
Abstract: The combination of unstable hydrogen storage materials with a high pressure tank provides a potential solution to on-board hydrogen storage system for fuel cell vehicles. However, none of the available solid-state materials can fulfill all the requirements. In this work, ZrFeV-based alloys were systematically investigated for the possible use in such kind of hybrid storage devices. Among these alloys studied here, the composition (Zr0.7 Ti0.3 )1.04 Fe1.8 V0.2 shows the best overall properties with a reversible hydrogen capacity of 1.51 wt%, and a hydrogen desorption pressure of 11.2 atm at 0 °C. Besides, this alloy also shows excellent stability without obvious capacity loss even after 200 hydrogen absorption/desorption cycles. Calculated results show that the gravimetric density of the hybrid storage system combining a 35 MPa high pressure tank with (Zr0.7 Ti0.3 )1.04 Fe1.8 V0.2 alloy is 1.95 wt% when the volumetric density reaches 40 kg/m 3 . Highlights: (Zr0.7 Ti0.3 )1.04 Fe1.8 V0.2 alloy is optimized to have the best overall properties. (Zr0.7 Ti0.3 )1.04 Fe1.8 V0.2 alloy shows no obvious capacity loss after 200 cycles. A hybrid hydrogen storage system based on (Zr0.7 Ti0.3 )1.04 Fe1.8 V0.2 is proposed. ZrTiFeV alloy is a potential candidate for high pressure MH tank of fuel cell.